Enhancement of the reliability of MEMS shock sensors by adopting a dual-mass model. (1st March 2020) - Fathalilou, Mohammad; Soltani, Kamran; Rezazadeh, Ghader; Cigeroglu, Ender
Highlights: We proposed a dual-mass system for increasing the reliability of the shock sensors. It decreased the interval between the threshold, and the minimum shock up to 48% Optimum design parameters were obtained for increasing the reliability. Abstract: MEMS shock sensors are widely used with applications ranging from aircraft to electrical measurement systems. They are designed to operate at the shocks above a predefined threshold level. The conventional single-mass switches may lose their reliability at shock levels smaller than the threshold, if experience smaller unwanted pulse duration. This paper has proposed a dual-mass switch with auxiliary mass-spring attached to the main system which increases the reliability of the sensor against the unwanted pulse durations. By providing a mathematical model, the shock response spectrum of the novel system has been obtained and shown that by changing the system parameters, the peak amplitude of the main mass can be tuned to a minimum value. Moreover, the interval between the designed threshold, and the minimum shock which leads to switch at smaller unwanted pulse durations, has been decreased up to 45% in the proposed dual-mass model compared to the conventional one.